Let $G_n = \tfrac{1}{2}n(3n-1)$ be the pentagonal number for all $n\in \mathbb{Z}$ and $p(n)$ be the partition function. I was trying to prove one of the Ramanujan's congruences: $$p(5n-1) = 0 \pmod 5,$$ and my "brute force" proof reduces to show the following identity: $$\left(\sum_{G_n = 0 \pmod 5}(-1)^nq^{G_n}\right)\left(\sum_{G_n = 2 \pmod 5}(-1)^nq^{G_n}\right) + \left(\sum_{G_n = 1 \pmod 5}(-1)^nq^{G_n}\right)^2 = 0 \pmod 5,$$ where the sums are over all $n\in \mathbb{Z}$. After expanding a few terms (up to $q^{15000}$) of the left hand side of the identity, I strongly believe the following identity holds:

$$\left(\sum_{G_n = 0 \pmod 5}(-1)^nq^{G_n}\right)\left(\sum_{G_n = 2 \pmod 5}(-1)^nq^{G_n}\right) + \left(\sum_{G_n = 1 \pmod 5}(-1)^nq^{G_n}\right)^2 = 0.$$

I am in particular interested in a proof of the last identity.

Update: Here is what I tried. Denote by $$F_k(q) := \sum_{G_n=k\pmod 5}(-1)^nq^{G_n}.$$ Notice that $G_n = 1 \pmod 5$ if and only if $n = 1 \pmod 5$, and $G_{5k+1} = 1 + 25G_{-k}$. This would give $F_1(q) = q\prod_{m=1}^{\infty}(1-q^{25m})$ using the pentagonal number theorem. However, I do not know a way to factor $F_0(q)$ and $F_2(q)$.

  • $\begingroup$ we have $G_{5k}\equiv G_{5k+2}\equiv0\mod5$ and $G_{5k+3}\equiv G_{5k+4}\equiv2\mod5$ $\endgroup$ – JonMark Perry Mar 16 '16 at 6:51

It turns out that Ramanujan has asserted a result, from which the identity in the question follows. In order to state his result, recall the $q$-Pochhammer symbols $(a;q)_\infty = \prod_{k \ge 0}(1-aq^n)$. For convenience, we always suppress the subscript $(a;q) = (a;q)_\infty$.

Ramanujan asserted that,

$$(q;q) = \frac{(q^{10};q^{25})(q^{15};q^{25})(q^{25};q^{25})}{(q^{5};q^{25})(q^{20};q^{25})} - q(q^{25};q^{25})-q^2\frac{(q^{5};q^{25})(q^{20};q^{25})(q^{25};q^{25})}{(q^{10};q^{25})(q^{15};q^{25})}.$$

The pentagonal number theorem says that the left hand side $(q;q) = \sum_n (-1)^nq^{G_n}$. However the right hand side decomposes the sum based on $G_n\bmod 5$. Using the notation $F_k$ defined in the question, we obtain $$F_0 = \frac{(q^{10};q^{25})(q^{15};q^{25})(q^{25};q^{25})}{(q^{5};q^{25})(q^{20};q^{25})}, F_1 = - q(q^{25};q^{25}), F_2=-q^2\frac{(q^{5};q^{25})(q^{20};q^{25})(q^{25};q^{25})}{(q^{10};q^{25})(q^{15};q^{25})}.$$ Clearly, $F_0F_2 + F_1^2 = 0$.

Inspired by the proof of the Ramanujan's identity on $(q;q)$ in Ramanujan's "most beautiful identity" by Hirschhorn, here is a slightly direct proof of $F_0F_2 + F_1^2=0$.

Recall the Jacobi triple product: $(a^{-1}; q)(aq; q)(q;q)=\sum_n(-1)^na^nq^{n(n+1)/2}$. If $a \neq 1$, then we have $$(a^{-1}q;q)(aq;q)(q;q)=\sum_n(-1)^n\frac{a^n}{1-a^{-1}}q^{n(n+1)/2}.$$ Replacing $a$ by $a^{-1}$, we get $$(aq;q)(a^{-1}q;q)(q;q)=\sum_n(-1)^n\frac{a^{-n}}{1-a}q^{n(n+1)/2}.$$

Averaging the last two identities, we obtain $$(a^{-1}q;q)(aq;q)(q;q)=\sum_n(-1)^n\frac{1}{2}\left(\frac{a^n}{1-a^{-1}}+\frac{a^{-n}}{1-a}\right)q^{n(n+1)/2}.$$

Let $\omega := e^{2\pi i/5}$ be a (primitive) 5th root of unity. Take $a = \omega$, we have $$(\omega^{-1}q;q)(\omega q;q)(q;q)=\sum_n(-1)^nc_nq^{n(n+1)/2},$$ where $$c_n = \frac{1}{2}\left(\frac{\omega^n}{1-\omega^{-1}}+\frac{\omega^{-n}}{1-\omega}\right) = \begin{cases}\frac{1}{2} & \text{if }n=0\pmod 5 \\ \frac{1+\sqrt{5}}{4} & \text{if }n=1\pmod 5 \\ 0 & \text{if }n=2\pmod 5 \\ -\frac{1+\sqrt{5}}{4} & \text{if }n=3\pmod 5 \\ -\frac{1}{2} & \text{if }n=4\pmod 5\end{cases}.$$

So $(\omega^{-1}q;q)(\omega q;q)(q;q) = \frac{1}{2}(C_0 + \phi_1 C_1 - \phi_1 C_3 - C_4)$, where $C_i = \sum_{n=i\pmod 5}(-1)^nq^{n(n+1)/2}$ and $\phi_1 = \frac{1+\sqrt{5}}{2}$. Notice that by replacing $n$ by $-(n+1)$ in the sums, one can show that $C_0 = -C_4$ and $C_1 = - C_3$. So we get $$(\omega^{-1}q;q)(\omega q;q)(q;q) = C_0+\phi_1 C_1.$$

Similarly, take $a = \omega^2$ and obtain $$(\omega^{-2}q;q)(\omega^2 q;q)(q;q) = \frac{1}{2}(C_0+\phi_2C_1-\phi_2C_3-C_4)=C_0+\phi_2C_1,$$ where $\phi_2 = \frac{1-\sqrt{5}}{2}$. Multiply the last two identities, we have $$(\omega^{-2}q;q)(\omega^{-1}q;q)(\omega q;q)(\omega^{2}q;q)(q;q)(q;q) = C_0^2-C_0C_1-C_1^2.$$ Since $(\omega^{-2}q;q)(\omega^{-1}q;q)(\omega q;q)(\omega^{2}q;q)(q;q) = (q^5;q^5),$ we have $$(q;q)=\frac{C_0^2-C_0C_1-C_1^2}{(q^5;q^5)}.$$ By the same reasoning we used at the very beginning, we have $$F_0 = \frac{C_0^2}{(q^5;q^5)}, F_1 = \frac{-C_0C_1}{(q^5;q^5)}, F_2 = \frac{-C_1^2}{(q^5;q^5)}.$$

Remark: With a bit of extra work (using Jacobi triple product), one can show $C_0 = (q^{10};q^{25})(q^{15};q^{25})(q^{25};q^{25}), C_1 = (q^5;q^{25})(q^{20};q^{25})(q^{25};q^{25})$ and hence derive Ramanujan's identity.


I can't seem to prove the identity, but I can show you what I've got.

$G_{5k}\equiv G_{5k+2}\equiv0\mod5$

which can easily be seen in the $5k$ case, and for $5k+2$ we have: $$\dfrac{(5k+2)(3(5k+2)-1)}{2}$$ $$=\dfrac{(5k+2)(15k+5)}{2}$$ $$=\dfrac{5(5k+2)(3k+1)}{2}$$

$G_{5k+3}\equiv G_{5k+4}\equiv2\mod5$

The $2$ cases have very similar proofs, here is for $5k+3$:

$$\dfrac{(5k+3)(3(5k+3)-1)}{2}$$ $$=\dfrac{(5k+3)(15k+8)}{2}$$ $$=\dfrac{75k^2+85k+24}{2}$$

As $5$ is not divisible by $2$, the remainder is $\dfrac{24}{2}\equiv2\mod5$.

Next we can expand the expressions for $G_n$ to get relations between them.

$$G_{5k}=\dfrac{75k^2-5k}{2}$$ $$G_{5k+2}=\dfrac{75k^2+55k+10}{2}$$

Adding the two gives:


$$G_{5k+3}=\dfrac{75k^2+85k+24}{2}$$ $$G_{5k+4}=\dfrac{75k^2+115k+44}{2}$$

Subtracting the two gives:


as I can't seem to get the square and the linear component to form a valid ratio either!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.